Alternative Culture Medium for Bacterial Growth Using Chicory Roots Extract. - Fitua Minuar Aziz (College of Pharmacy / Mustansiriyah University, 2014)
This is the first study to test the using of hot water extract of Cichorium intybus (chicory) of roots as alternative medium for Bacterial growth. The tested bacteria were: Staphylococcus aureus, Streptococcus pneumoniae, Escherichia coli, Klebsiella pneumoniae, Proteus vulgaris, Pseudomonas aeruginosa, Salmonella typhi and Acinetobacter spp.The results showed heavy growth of all tested bacteria after incubation at 37oC for 24hrs. In conclusion, Cichorium intybus (chicory) roots medium is a good source of nutrients, in both solid and liquid media, due to it contains of proteins, fructoligosaccharide (inulin) and elements and can used as alternative medium.